Effect of stearic acid on in-vitro formation of sheep oocytes - FARMAN, MOHAMED; NANDI, S; KUMAR, V GIRISH; TRIPATHI, SHIV KUMAR; GUPTA, P S P (The Indian Journal of Animal Sciences, 2015)
The present study was undertaken to study the effect of stearic acid (SA), a non esterified fatty acid (NEFA) on oocyte development of ewes (Ovis aries). Sheep oocytes were matured in vitro in the presence of different concentration of stearic acid (0 μM, 10 μM, 20 μM, and 30 μM) for 24h. After in vitro maturation, oocytes were in vitro inseminated with cauda epidydimus sperm processed with BO medium with concentration of 2 million sperms/ml and cultured on oviductal cell culture for 8 days. Oocytes were evaluated for cleavage and fertilization rates and after 7–8 days post insemination zygotes were evaluated for moruale /blastocyst stages. The maturation, cleavage and morulae/ blastocyst production rates were significantly lowered in media containing 20 μM stearic acid. Increment of stearic acid to 30 μM in media further reduced the maturation, cleavage and morulae/ blastocyst production. In conclusion, the metabolic stressors NEFA (SA) impaired the maturation, viability, cleavage and embryo production rates at the level 20 μM in ewes.